DAMPAK PERCERAIAN ORANG TUA TERHADAP HAK DAN KEWAJIBAN ANAK - Kismullah habib; Dhiauddin Tanjung; Irwansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of parental divorce on the fulfillment of children’s rights and obligations, particularly concerning the rights to financial support, education, care, and protection after divorce. This research employs a normative legal research method with a qualitative approach, focusing on the examination of legal norms governing parental obligations and the protection of children’s rights following divorce. The approaches used include statutory and conceptual approaches by reviewing relevant laws and regulations, legal doctrines, and previous studies related to children’s rights after divorce. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed using a qualitative-descriptive method. The results of the study indicate that, juridically, divorce does not eliminate parents’ obligations toward their children, as stipulated in the Marriage Law, the Compilation of Islamic Law, and child protection regulations. However, in practice, various problems are still found in fulfilling children’s rights after divorce. The findings reveal that the obligation to provide child support is often not carried out optimally, the fulfillment of children’s educational rights is hindered, child care tends to be borne by only one parent, and children’s psychological protection is weakened due to post-divorce conflicts. Therefore, parental divorce has a real impact on the neglect of children’s fundamental rights, highlighting the need to increase parents’ legal awareness, strengthen the active role of the courts, and enhance law enforcement to ensure the fulfillment of children’s rights and their best interests after divorce.